2011
DOI: 10.1111/j.1948-7134.2011.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

The sand fly fauna (Psychodidae: Phlebotominae) in the region of Saquarema, State of Rio de Janeiro, Brazil, an endemic area of cutaneous leishmaniasis transmission

Abstract: Cutaneous leishmaniasis, caused by Leishmania (Viannia) braziliensis, is sporadic in many rural and suburban areas of Rio de Janeiro State. An investigation was carried out during 2008/9 in the Municipality of Saquarema, Rio de Janeiro, Southeast Brazil, in order to identify the phlebotomine sand fly fauna. More than 2,100 sand flies were collected in peridomestic areas in two chicken coops using CDC light traps. Nine species of phlebotomine sand flies were identified: Nyssomyia intermedia, Nyssomyia whitmani,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
(18 reference statements)
1
7
0
2
Order By: Relevance
“…All of the species found in this work have been recorded in other regions of RJ ( de Aguiar et al 1986 , Rangel et al 1990 , Brazil et al 1991, 2011 , Oliveira et al 1995 , Souza et al 2003 , Alves 2007 ). Evandromyia was the most abundant genus in the collections, represented by the species Ev.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…All of the species found in this work have been recorded in other regions of RJ ( de Aguiar et al 1986 , Rangel et al 1990 , Brazil et al 1991, 2011 , Oliveira et al 1995 , Souza et al 2003 , Alves 2007 ). Evandromyia was the most abundant genus in the collections, represented by the species Ev.…”
supporting
confidence: 64%
“…Migonemyia was the second most abundant genus and was represented only by the species Mg. migonei , which was the second most frequent. This species is widely distributed in all regions of Brazil and it has been recorded throughout almost the entire RJ ( Rangel et al 1986 , Brazil et al 1991, 2011 , Souza et al 2002, 2003 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Its sylvatic origin has been discussed elsewhere [ 1 ]. This suggests that, in Ilha Grande, L. (L.) longipalpis is probably more common in forest areas, as it was also found in other Atlantic Forest areas of Rio de Janeiro, Espírito Santo and São Paulo States [ 36 , 57 - 60 ].…”
Section: Discussionmentioning
confidence: 73%
“…More recently, Brazil et al (8) and Rodrigues et al (9) showed the presence of Lu. longipalpis in transition areas of Atlantic Forest in Saquarema and Niterói, respectively.…”
mentioning
confidence: 99%